On applications of the fractional calculus for some singular differential equations - Ozturk, Okkes; Yilmazer, Resat (Natural Sciences Publishing, 2018)
Generalized Leibniz rule and some theorems in the calculus of the fractional derivatives and integrals was used to obtain the fractional solutions of the radial Schrödinger equation transformed into a singular differential equation and, these solutions were also exhibited as hypergeometric notations. © 2018 NSP.
Keywords: Fractional calculus; Fractional calculus theorems; Generalized Leibniz rule; Radial Schrödinger equation